2021
DOI: 10.1186/s12889-021-10846-1
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle habits and depressive symptoms in Norwegian adolescents: a national cross-sectional study

Abstract: Background This study’s purpose was to examine the association between a broad range of lifestyle habits and depressive symptoms in Norwegian adolescents. Methods This study was based on national, self-reported, cross-sectional data from the Ungdata Surveys, conducted in 2017–2019. The target group comprised 244,250 adolescents (ages 13–19). Binominal logistic regression was used to analyse the association between lifestyle habits (physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 62 publications
2
23
0
1
Order By: Relevance
“…In keeping with previous findings ( 64 ), this current study found a significant association between physical activity and depression ( Table 3 ). Respondents with low physical activity reported more depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…In keeping with previous findings ( 64 ), this current study found a significant association between physical activity and depression ( Table 3 ). Respondents with low physical activity reported more depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…[ 46 ] Another cross-sectional study of 244,250 Norwegian adolescents aged 13–19 showed that those with higher overall adherence to recommendations for physical activity, screen time, tobacco smoking, and alcohol consumption had up to 60% lower odds of depressive symptoms. [ 47 ] Although results reported in these studies are encouraging, prospective effect estimates are more reliable since they consider baseline levels of mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence suggests that poor diet is a relevant predictor in the onset of depressive illness [ 22 ], whereas healthy eating patterns may reduce anxiety symptoms [ 23 ]. The consumption of specific food items and beverages, such as high consumption of fruit, whole grain bread and fish and low consumption of sugar-sweetened beverages, was also associated with lower levels of depressive symptoms in adolescents [ 24 ] and lower risk of mental distress among adults [ 25 ]. Some studies suggest an association of higher consumption levels of proinflammatory diets and Western diets with the increased incidence of depression, while higher intake of fruits and vegetables was associated with lower incidence of depression [ 26 ].…”
Section: Introductionmentioning
confidence: 99%